Genetic parameter estimation for beef bull fertility: a review - Semler, Michael Wayne (My University, 2024)
Reproductive efficiency is the major driver of profitability and genetic performance among all livestock species; advancements in husbandry practices and genetic selection tools to increase reproductive output have been well documented for cow fertility, but largely ignored for beef bull fertility in research and published literature. Estimation of beef sire fertility is economically relevant to not only the U.S. beef herd, but to the world, as the economic losses from sub fertile bulls and late pregnancies can have major implications on profitability while slowing genetic progress. Published studies that have assessed the genetic parameters of beef bull fertility traits are sparse in number, but indicate low to moderate heritability estimates for semen quality traits. Correlations amongst semen quality traits are also low to moderate, but favorable, indicating that indirect selection could provide opportunity for genetic advancement of particular traits. Genomic selection continues to make strides forward within the beef industry among other performance traits but has been underdeveloped in terms of fertility selection. Quantitative trait loci (QTL) for bull fertility discovered in dairy cattle have provided a basis for further research and examples of sire selection methods, however separations in management practices and slower adoption of AI forces the beef industry to look for other opportunities for data collection of phenotypic fertility traits. Ultimately, improvements in beef bull fertility have the potential to significantly impact the profitability of the global beef system by reducing cost, increasing selection intensity, and rapidly increasing genetic gain. Research regarding estimation of the genetic parameters of beef bull semen quality traits, development of genomic selection tools for fertility, and utilization of breeding soundness examination (BSE) records to provide valuable fertility phenotypes is gravely needed to make advancements in bull fertility a reality. The objective of this report is to discuss the various literature surrounding male fertility genetic parameters within both the beef and dairy industries.
Keywords: Bull; Beef; Fertility; Genetic parameter estimation